Untangling Photofaradaic and Photocapacitive Effects in Organic Optoelectronic Stimulation Devices - Ðerek, Vedran; Rand, David; Migliaccio, Ludovico; Hanein, Yael; Głowacki, Eric Daniel (Frontiers in Bioengineering and Biotechnology, 2020)
Light, as a versatile and non-invasive means to elicit a physiological response, offer solutions to problems in basic research as well as biomedical technologies. The complexity and limitations of optogenetic methods motivate research and development of optoelectronic alternatives. A recently growing subset of approaches relies on organic semiconductors as the active light absorber. Organic semiconductors stand out due to their high optical absorbance coefficients, mechanical flexibility, ability to operate in wet environment, and potential biocompatibility. They, therefore, can enable ultrathin and minimally invasive form factors not accessible with traditional inorganic matebrials. Organic semiconductors, upon photoexcitation in an aqueous medium, can transduce light into 1) Photothermal heating, 2) photochemical/photocatalytic redox reactions, 3) photocapacitive charging of electrolytic double layers, and 4) photofaradaic reactions. In realistic conditions, different effects may coexist, and understanding their role on observed physiological phenomena is an area of critical interest. This article serves to critically evaluate the emerging picture of photofaradaic versus photocapacitive effects in the context of our group’s research efforts and that of others over the past few years. We present simple experiments which can be used to benchmark organic optoelectronic stimulation devices.